2000
DOI: 10.1592/phco.20.3.166.34783
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized Antimicrobial Therapy in Acutely Ill Patients

Abstract: Recent data are sparking renewed interest in therapy with aerosolized antimicrobials in critically ill patients as well as other populations such as those with neutropenia, human immunodeficiency virus infection, and cystic fibrosis. Pneumonia is a common complication in these patients and is associated with substantial morbidity and increased mortality. Clinical trials evaluated aerosolized antimicrobials for the prevention and treatment of pneumonia in hospitalized patients. In addition, factors that affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 130 publications
0
28
0
1
Order By: Relevance
“…Recent data have renewed interest in therapy of critically ill patients using aerosolized antimicrobials [12], because this method of administration offers the advantage of higher concentrations of antibiotic at the site of infection [11], enhanced and faster bacterial killing [13,14], and low systemic toxicity [15,16] compared with intravenous (IV) administration. One trial of prophylactic aerosolized ceftazidime showed that it was efficacious in preventing VAP without promoting antimicrobial resistance [17].…”
Section: Hallal Et Almentioning
confidence: 99%
“…Recent data have renewed interest in therapy of critically ill patients using aerosolized antimicrobials [12], because this method of administration offers the advantage of higher concentrations of antibiotic at the site of infection [11], enhanced and faster bacterial killing [13,14], and low systemic toxicity [15,16] compared with intravenous (IV) administration. One trial of prophylactic aerosolized ceftazidime showed that it was efficacious in preventing VAP without promoting antimicrobial resistance [17].…”
Section: Hallal Et Almentioning
confidence: 99%
“…Клинические и экономические последствия ин фекций, вызванных резистентными микроорганиз мами, и отсутствие новых антибиотиков, активных по отношению к этим патогенам, стимулируют интерес к более широкому использованию ингаля ционных антибактериальных препаратов [15]. Дока зана высокая эффективность применения ингаляци онных антибиотиков (тобрамицина, колистиметата и др.)…”
Section: заметки из практикиunclassified
“…Clinical and economical consequences of multiresis tance of bacteria to ABD and lack of new ABD active against those pathogens stimulated the inhalationt use of ABD [10], the efficacy of which was proved in cystic fibro sis patients [11,12]. Inhalation allows maintaining the high concentration of the medication in the infection area [13] resulting in better bacterial killing [14,15] and lowing both systemic absorption of medication and toxicity [16].…”
Section: Introductionmentioning
confidence: 99%